TARAS SHEVCHENKO AND IDENTITY OF UKRAINIAN LITERARY TRADITION - Krysa , B. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article raises the problem of artistic realisation of traditional for Ukrainian literature Christian principles of life. The author deduces religiosity and human morality which influenced the creative work of Taras Shevchenko from the ideological and aesthetic poetry world of the genius of the Ukrainian nation.